Experimental Investigation of the Performance of CPC under Local Weather Condition - Ngai, Seak Jie (IRC, 2018)

(untitled)
Numerous studies have been conducted by researchers to study the performance of Compound Parabolic Concentrator Collector (CPC) over the years. However, there are very few research papers related to performance of CPC Collector under tropical rainforest country such as Malaysia, where the environment has high proportion of diffuse solar radiation. Experimental evaluation of CPC collector has not been assessed in Malaysia. Thus, this project proposed to experimentally assess the performance of CPC Collectors under Malaysia’s weather condition. A CPC collector experimental rig was set up at STARC Lab, Universiti Teknologi PETRONAS, consisting of three evacuated flow through absorbers. Various parameters related to heat transfer were recorded and analyzed. From the experimentation, temperature output can go up to 109.1°C on a day with high intensity of solar radiation whereas the temperature output can go up to 75.8°C on a day with low intensity of solar radiation. In addition, the performance of CPC collector has the same pattern with the temperature variation pattern of the day.